Um relato etnográfco sobre imaterialidades dos Luso-Bnei-Anussim no Nordeste português - Pignatelli, Marina (Trabalhos de Antropologia e Etnologia, 2020)
We call them Anousim (pl of Anous, which means forced or coerced into Hebrew), also known as Marranos, Conversos, Tornadiços, People of the Nation, New Christians or Jews to those who remained in Portugal and Spain and practiced their Judaism in secret, or those who left the Iberian Peninsula due to the Expulsion (1497) and the Inquisition (1536-1821), many having continued to freely practice Judaism in the diaspora. We know, however, that those Jews or New Christians who remained on Lusitanian soil have adopted and maintained various discrete or hidden strategies to resist forced conversion to the present. We also know of many Portuguese, who insist on an identification with the Jewish matrix and of an unprecedented effort to recover what remains of the vestiges of the memory of this Jewish culture in Portugal. There is an intense revivalist activity around the Jewish cultural heritage in the country. What we do not know is to what extent such Jewish identity processes and mnemonic materialities and immaterialities persist today in the public and private sphere, and how these cultural traits coexist with the national fabrication of heritage in its various material and discursive aspects. The study focuses on the latter, through the ethnographic method.